Transformation for sustainable business and management practices : exploring the spectrum of industry 5.0 - Saini, Aarti; Garg, Vikas (Emerald Publishing Limited, 2023)
Since the introduction of Industry 5.0, there has been a greater emphasis on the human-centric view in human-machine collaboration. As society has benefitted from technological advancements in all aspects of industrial sectors, there has been a rethinking of the role human beings should play in future evolutions. This includes the skills or knowledge the workforce should adopt in training, and how the positive outcomes of such advancements can be maximized in the economy whilst mitigating the negative ethical and social consequences. Transformation for Sustainable Business and Management Practices: Exploring the Spectrum of Industry 5.0 provides an understanding of the foundations of these predicted changes; how the transformation started, evolved, and accelerated over time.